Effects of anaesthesia and analgesia on long-term outcome after total knee replacement: A prospective, observational, multicentre study. Issue 10 (October 2017) - Bugada, Dario; Allegri, Massimo; Gemma, Marco; Ambrosoli, Andrea L.; Gazzerro, Giuseppe; Chiumiento, Fernando; Dongu, Doriana; Nobili, Fiorella; Fanelli, Andrea; Ferrua, Paolo; Berruto, Massimo; Cappelleri, Gianluca
Abstract : BACKGROUND: Perioperative regional anaesthesia may protect from persistent postsurgical pain (PPSP) and improve outcome after total knee arthroplasty (TKA). OBJECTIVES: Aim of this study was to evaluate the impact of regional anaesthesia on PPSP and long-term functional outcome after TKA. DESIGN: A web-based prospective observational registry. SETTING: Five Italian Private and University Hospitals from 2012 to 2015. PATIENTS: Undergoing primary unilateral TKA, aged more than 18 years, informed consent, American Society of Anesthesiologists (ASA) physical status classes 1 to 3, no previous knee surgery. INTERVENTION(S): Personal data (age, sex, BMI and ASA class), preoperative pain assessed by numerical rating scale (NRS) score, and risk factors for PPSP were registered preoperatively. Data on anaesthetic and analgesic techniques were collected. Postoperative pain (NRS), analgesic consumption, major complications and patient satisfaction were registered up to the time of discharge. PPSP was assessed by a blinded investigator during a phone call after 1, 3 and 6 months, together with patient satisfaction, quality of life (QOL) and walking ability. MAIN OUTCOME MEASURES: Experience of PPSP according to the type of peri-operative analgesia. RESULTS: Five hundred sixty-three patients completed the follow-up. At 6 months, 21.6% of patients experienced PPSP, whereas autonomy was improved only in 56.3%; QOL was worsened or unchanged in 30.7% of patients and improved in 69.3%. Patients receiving continuous regional anaesthesia (epidural or peripheral nerve block) showed a lower NRS through the whole peri-operative period up to 1 month compared with both single shot peripheral nerve block and those who did not receive any type of regional anaesthesia. No difference was found between these latter two groups. Differences in PPSP at 3 or 6 months were not significantly affected by the type of anaesthesia or postoperative analgesia. A higher NRS score at 1 month, younger age, history of anxiety or depression, pro-inflammatory status, higher BMI and a lower ASA physical status were associated with a higher incidence of PPSP and worsened QOL at 6 months. CONCLUSION: Continuous regional anaesthesia provides analgesic benefit for up to 1 month after surgery, but did not influence PPSP at 6 months. Better pain control at 1 month was associated with reduced PPSP. Patients with higher expectations from surgery, enhanced basal inflammation and a pessimistic outlook are more prone to develop PPSP. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT02147730 Abstract : Supplemental Digital Content is available in the text